2009
DOI: 10.1103/physrevb.79.125201
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetic properties of monoclinicβ-Cu2V2O7: AGGA

Abstract: A first-principles study on monoclinic C2 / c copper pyrovanadate ␤-Cu 2 V 2 O 7 has been performed using the generalized gradient approximation ͑GGA͒ and GGA+ U method. The optimized unit-cell parameters and atomic coordinates of ␤-Cu 2 V 2 O 7 agree well with experimental data. The optimized crystal structure of ␤-Cu 2 V 2 O 7 indicates the existence of one-dimensional -Cu-Cu-Cu-Cu-chains. The electronic structure and magnetic properties were evaluated by the GGA+ U calculations, which indicate that the ␤-Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Further on, band structure calculations suggested two alternating couplings along the spin chains. 25 Surprisingly, all the three proposals are quite different from the actual spin lattice. Below we demonstrate that empirical considerations in the experimental studies 23,24,26 do not take account of the peculiar electronic structure of β-Cu 2 V 2 O 7 , while the computational study 25 failed to resolve all the relevant exchange interactions in the compound.…”
Section: Crystal Structure and Magnetic Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Further on, band structure calculations suggested two alternating couplings along the spin chains. 25 Surprisingly, all the three proposals are quite different from the actual spin lattice. Below we demonstrate that empirical considerations in the experimental studies 23,24,26 do not take account of the peculiar electronic structure of β-Cu 2 V 2 O 7 , while the computational study 25 failed to resolve all the relevant exchange interactions in the compound.…”
Section: Crystal Structure and Magnetic Propertiesmentioning
confidence: 97%
“…[19][20][21][22] In the following, we provide an instructive example that demonstrates the relevance of these characteristics for the microscopic magnetic model. We show that the β-modification of Cu 2 V 2 O 7 , previously considered as a spin-chain or a spin-dimer compound, [23][24][25] is the best available realization of the spin- 1 2 Heisenberg model on the honeycomb lattice. To arrive at this unexpected conclusion, we first examine the crystal structure and analyze available experimental results (Sec.…”
Section: Introductionmentioning
confidence: 99%
“…47 Since the TRMC shows that there is only minor wavelength dependency on the carrier mobility and lifetime in Cu 2 V 2 O 7 , we attribute the sharp increase in the IPCE of Cu 2 V 2 O 7 below 350 nm to a wavelength-dependent photogeneration yield in this material. Indeed, the first electronic transition in Cu 2 V 2 O 7 is a Laporte-forbidden Cu dd transition, 31,35 like in hematite. It has been suggested that such transitions do not significantly contribute to the photocurrent.…”
Section: Photoelectrochemical Propertiesmentioning
confidence: 99%
“…the antiferromagnetic ground state at 0 K. 22 We perform calculations within many-body perturbation theory through the use of the self-consistent QSGW technique. An efficient exchange-correlation kernel is included to account for vertex corrections, as described in…”
Section: Graphical Toc Entrymentioning
confidence: 99%